Effect of Gamma Irradiation on Bioactive Compounds and Antioxidant Activities of Boesenbergia rotunda (L.) Mansf. and Prediction of Flavonoid Stability Using Factorial Design - Monton, Chaowalit; Suwanbumrungchai, Keeratikorn; Salaemae, Hanaduha; Saniwee, Nalina; Wunnakup, Thaniya; Charoenchai, Laksana; Theanphong, Orawan; Chankana, Natawat; Suksaeree, Jirapornchai; Rangsimawong, Worranan (Trends in Sciences, 2025)
Flavonoids are bioactive compounds found in the roots and rhizomes of Boesenbergia rotunda (L.) Mansf. Stability data for these flavonoids, including pinocembrin, pinostrobin, and panduratin A, remain limited, particularly for gamma-irradiated samples. This study evaluated the impact of gamma irradiation on flavonoid contents, antioxidant activities, and predicted flavonoid stability using factorial design. Thirty-two B. rotunda samples from various locations of Thailand were gamma-irradiated with 12.3 - 27.5 kGy. High-performance liquid chromatography assessed flavonoid levels, while antioxidant activities were measured via DPPH radical scavenging, ABTS cation radical decolorization, and superoxide anion radical scavenging assays. Results showed slight reductions in pinocembrin and panduratin A levels, with pinostrobin levels preserved. Antioxidant activities decreased, except for nitric oxide scavenging activity, which remained stable. Flavonoid stability predictions were made by analyzing initial flavonoid contents and monitoring samples stored at 30 °C/75% RH and 40 °C/75% RH for 90 and 180 days. Flavonoids were more stable in rhizomes than roots. Among flavonoids, pinostrobin showed the highest stability, followed by pinocembrin and panduratin A. Predicted lowest retention in roots were 67.50%, 89.20% and 6.84%, respectively, compared to 91.83%, 99.92% and 35.99% in rhizomes. Gamma irradiation reduced flavonoid contents and antioxidant activities. The study introduced factorial design as a predictive tool for flavonoid stability in B. rotunda, aiding the preservation of bioactive compounds. However, longer-term studies are necessary to predict extended stability trends. HIGHLIGHTS Gamma irradiation slightly decreased pinocembrin and panduratin A but preserved pinostrobin in B. rotunda. Antioxidant activities were reduced, except for nitric oxide scavenging activity. Flavonoids in rhizomes were more stable than those in roots during storage. Response surface modeling predicted flavonoid stability, with pinostrobin most stable, followed by pinocembrin and panduratin A in roots and rhizomes. GRAPHICAL ABSTRACT